Students’ Learning Trajectory in Solving Fraction Problems: Cases of Boy and Girl Students in Junior High School - Muh Rizal; Tatag Yuli Eko Siswono; Nurdin; Tria Bitara (Studies in Learning and Teaching, 2023)
This study aims to describe the learning trajectories of male and female students in solving fraction problems. The research subjects consisted of a male student and a female student who had the same mathematical ability. Learning trajectory data for both subjects were taken through fractional problem solving tests and in-depth interviews. Observations focused on the four stages of problem solving strategies, namely understand the problem, divide a plan, carry out the plan, and look back. Data analysis begins with examining all data, reducing data, grouping data, categorizing, coding, and finally checking data through time triangulation. The results of the study show that in understanding the problem, boys identify goals and information to solve the problem to state its completeness, and girls identify information to solve the problem to state its completeness. In making plans, girls complete in detail and involve many concepts, while boys only have one concept, so girls' learning trajectories are longer. While carrying out the plan, the two solve problems according to the plan. Looking back, girls used more than one method alternative while boys only used one alternative.